2007
DOI: 10.1111/j.1365-2273.2007.01468.x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized controlled trial of coblation tonsillectomy versus dissection tonsillectomy with bipolar diathermy haemostasis

Abstract: Objectives: To compare postoperative recovery in children between 4 and 12 years undergoing tonsillectomy, using either coblation tonsillectomy or dissection tonsillectomy with bipolar diathermy haemostasis. Design: A prospective, single blind, randomised controlled trial. Setting: ENT clinic, University Teaching Hospital. Participants: Forty paediatric patients, aged between 4 and 12 years and between 16 and 60 kg in weight with standard indication for tonsillectomy. Methods: Patients were randomly allocated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 17 publications
2
50
3
Order By: Relevance
“…11 The authors found that intra-operative bleeding was significantly less in the coblation group and patients undergoing coblation tonsillectomy reported less pain, quicker return to normal diet, quicker return to normal activity, and less use of analgesics over a 10-day period than patients undergoing dissection tonsillectomy.…”
Section: Discussionmentioning
confidence: 95%
“…11 The authors found that intra-operative bleeding was significantly less in the coblation group and patients undergoing coblation tonsillectomy reported less pain, quicker return to normal diet, quicker return to normal activity, and less use of analgesics over a 10-day period than patients undergoing dissection tonsillectomy.…”
Section: Discussionmentioning
confidence: 95%
“…The lower radiofrequency-generated energy employed by this technique means less tissue is damaged thus less inflammation and quicker wound healing which is translated to lesser postoperative pain, faster patient recovery, shorter hospital stay, and cheaper over-all cost of medical care. High quality studies, some in the form of randomised controlled trials (RCTs), have backed up these theoretical advantages of coblation surgery [2][3][4][7][8][9][10][11]. Chang et al [4] showed that it has lower early post-operative pain and likewise highlighted the ease of the procedure.…”
Section: Discussionmentioning
confidence: 97%
“…The advantages of coblation tonsillectomy over other techniques have been well reported, specifically the lower early phase post-operative pain and the ease of the procedure itself [2][3][4]. This surgical innovation has been practised in UK for almost a decade now.…”
Section: Introductionmentioning
confidence: 97%
“…The results showed an increased risk of secondary bleeding associated with ''hot'' techniques of dissection and haemostasis, although return to theatre rates were broadly similar [1,2]. Findings also included a higher secondary haemorrhage rate associated with coblation and single use instruments [1], but more recent work has found coblation, which is cold ablation, to be an excellent tool in terms of pain and secondary haemorrhage post-operatively [3][4][5][6][7]. The National Institute of Clinical Excellence commissioned a review of the safety and efficacy of monopolar and bipolar electrosurgery for tonsillectomy [8] and found that electrosurgery is associated with higher rates of secondary haemorrhage and return to theatre rates when compared to cold steel dissection and ties.…”
Section: Introductionmentioning
confidence: 94%